The Effect of Virtual Reality Box on Children Who Experience Anxiety during Primary Tooth Extraction - Joanita Athifah; Tiara Septa Risky; Atika Boneta; Yufen Widodo (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
Dental anxiety is a state of concern that something terrible will happen in connection with dental care or certain aspects of dental care. The level of dental anxiety was most commonly found in children (20, 48%). Therefore, an alternative to overcome this problem is to use a virtual reality box. This tool is designed to evoke a 3-dimensional atmosphere so that the user seems to be able to see in real. The purpose of this study was to determine the effect of the virtual reality box on the child's anxiety level at the time of primary tooth extraction. This research is a quasi-experimental research with a case-control design. With research subjects selected through Non-Probability Sampling with Purposive Sampling technique. With a total sample of 58 people consisting of children in the age category 6-12 years. Data were analyzed bivariately using Independent T Test. After the entire series of activities is carried out, then the distribution data results show a significance value lower than the probability value, which is 0.000 0.05. This shows that there is an effect of using a virtual reality box on the level of anxiety in children who have their primary teeth extracted.